WEBVTT
00:00:00.520 --> 00:00:03.430
Improper Integrals: Infinite Limits of Integration
00:00:04.250 --> 00:00:10.260
In this video, weβll learn how to evaluate improper integrals, where one or more of the endpoints approaches infinity.
00:00:10.880 --> 00:00:14.360
Weβll be looking at some examples of how we can solve integrals of this form.
00:00:15.150 --> 00:00:28.430
Now, letβs start by considering the following function π of π₯ and letβs consider an integral of this function π of π₯ with an infinite bound, so the integral from π to infinity of π of π₯ with respect to π₯.
00:00:28.980 --> 00:00:32.270
And we can let π be some point on our π₯-axis, say here.
00:00:32.780 --> 00:00:39.150
Then, this integral represents the area between π of π₯ and the π₯-axis from π to infinity.
00:00:40.060 --> 00:00:42.370
Now, this doesnβt really seem to make sense.
00:00:42.710 --> 00:00:45.850
How can infinity be a bound when itβs not a number?
00:00:46.360 --> 00:00:49.350
And how can we find an area that goes on to infinity?
00:00:50.040 --> 00:00:56.160
Now, although this doesnβt seem to make sense, it is in fact possible to evaluate certain integrals of this form.
00:00:56.690 --> 00:00:58.350
And we do this using limits.
00:00:58.760 --> 00:01:09.940
The formula we use to solve this integral tells us that this integral is equal to the limit as π‘ goes to infinity of the integral from π to π‘ of π of π₯ with respect to π₯, for π‘ greater than π.
00:01:10.410 --> 00:01:13.490
Itβs important to note that this only works in certain cases.
00:01:13.700 --> 00:01:19.170
Firstly, we require that the integral from π to π‘ of π of π₯ with respect to π₯ exists.
00:01:19.780 --> 00:01:21.790
So thatβs this integral in our formula.
00:01:22.550 --> 00:01:27.520
We also require that the limit of this integral as π‘ tends to infinity exists too.
00:01:28.100 --> 00:01:29.820
So thatβs this limit in our formula.
00:01:30.610 --> 00:01:39.960
Now, we can say that if both the integral and the limit exist, then we can say that our integral with an infinite limit, which is the integral weβre going to find, converges.
00:01:40.520 --> 00:01:48.330
And if either the integral does not exist or the limit does not exist, then we can say that our integral with infinite limit diverges.
00:01:49.480 --> 00:01:58.790
Just to recap, we can say that our integral from π to infinity of π of π₯ with respect to π₯ converges if it exists and is equal to some real constant π.
00:01:59.110 --> 00:02:04.940
And the integral from π to infinity of π of π₯ with respect to π₯ diverges if it does not exist.
00:02:05.950 --> 00:02:08.830
Letβs now look at an example of an integral of this form.
00:02:10.550 --> 00:02:15.860
The integral from one to infinity of one over π₯ squared with respect to π₯ is convergent.
00:02:16.220 --> 00:02:17.460
What does it converge to?
00:02:18.410 --> 00:02:21.330
In this question, weβre told that this integral is convergent.
00:02:21.810 --> 00:02:25.170
And this tells us that this integral does evaluate to some constant.
00:02:25.670 --> 00:02:40.150
We can find what this constant is by using the following formula, which tells us that the integral from π to infinity of π of π₯ with respect to π₯ is equal to the limit as π‘ goes to infinity of the integral from π to π‘ of π of π₯ with respect to π₯.
00:02:40.720 --> 00:02:48.000
Now, if you look at our integral, we can see the π is equal to one and π of π₯ is equal to one over π₯ squared.
00:02:48.530 --> 00:02:50.940
We can substitute these two into our formula.
00:02:51.580 --> 00:03:00.300
And we obtain that the integral is equal to the limit as π‘ tends to infinity of the integral from one to π‘ of one over π₯ squared with respect to π₯.
00:03:00.970 --> 00:03:02.790
We can start by finding this integral.
00:03:03.090 --> 00:03:06.620
We can rewrite one over π₯ squared as π₯ to the power of negative two.
00:03:07.160 --> 00:03:09.440
And then, we can use the power rule for integration.
00:03:09.710 --> 00:03:13.680
We increase the power by one and then divide by the new power.
00:03:14.190 --> 00:03:17.240
Increasing the power by one gives us π₯ to the power of negative one.
00:03:17.550 --> 00:03:19.020
And then, we divide by the new power.
00:03:19.020 --> 00:03:19.940
So thatβs negative one.
00:03:20.740 --> 00:03:23.130
And we mustnβt forget our bounds of π‘ and one.
00:03:23.640 --> 00:03:27.030
Now, dividing by negative one is the same as multiplying by negative one.
00:03:27.520 --> 00:03:30.700
And π₯ to the power of negative one is one over π₯.
00:03:31.130 --> 00:03:36.880
So we can rewrite π₯ to the power of negative one over negative one as negative one over π₯.
00:03:37.400 --> 00:03:39.320
Now, we can substitute in our bounds.
00:03:39.710 --> 00:03:43.010
Since π‘ is our upper bound, when we substitute it in, the sign remains the same.
00:03:43.410 --> 00:03:44.970
We get negative one over π‘.
00:03:45.260 --> 00:03:51.670
However, since one is our lower bound, we must change the sign when we substitute it in, giving us minus negative one over one.
00:03:52.000 --> 00:03:56.090
Simplifying this, we can see that our integral is equal to one minus one over π‘.
00:03:56.750 --> 00:03:59.100
And therefore, we can substitute this into our limit.
00:04:00.310 --> 00:04:09.170
And now, we have that the integral from one to infinity of one over π₯ squared with respect to π₯ is equal to the limit as π‘ tends to infinity of one minus one over π‘.
00:04:09.710 --> 00:04:12.050
Now, we can split this limit up using limit rules.
00:04:12.370 --> 00:04:21.330
We have that the limit of a difference of function, so π of π₯ minus π of π₯, is equal to the difference of the limits of the function, so the limit of π of π₯ minus the limit of π of π₯.
00:04:21.700 --> 00:04:29.130
We can apply this to our limit to say that it is equal to the limit as π‘ tends to infinity of one minus the limit as π‘ tends to infinity of one over π‘.
00:04:29.620 --> 00:04:33.930
Now, since one has no π‘ dependence, the limit as π‘ tends to infinity of one is simply one.
00:04:34.240 --> 00:04:37.480
And we can consider the limit as π‘ tends to infinity of one over π‘.
00:04:37.810 --> 00:04:41.050
As π‘ tends to infinity, π‘ is getting larger and larger and larger.
00:04:41.480 --> 00:04:45.610
Therefore, the reciprocal of π‘ or one over π‘ is getting closer and closer to zero.
00:04:45.950 --> 00:04:50.180
And so, we can say that the limit as π‘ tends to infinity of one over π‘ is equal to zero.
00:04:50.780 --> 00:05:00.070
And so here, we reach our solution, which is that the integral from one to infinity of one over π₯ squared with respect to π₯ converges to β and is therefore equal to β one.
00:05:02.360 --> 00:05:06.840
Next, we can take this formula for evaluating integrals with infinite limit one step further.
00:05:07.120 --> 00:05:10.720
We will be editing it slightly so we can evaluate integrals of a slightly different form.
00:05:11.270 --> 00:05:14.560
Letβs suppose we had a function π of π₯, which looks something like this.
00:05:14.950 --> 00:05:19.240
And suppose weβre asked to find the integral from negative infinity to π of π of π₯.
00:05:19.720 --> 00:05:21.830
Now, π can be any point on our π₯-axis.
00:05:21.880 --> 00:05:23.050
But letβs suppose itβs here.
00:05:23.520 --> 00:05:30.520
Now, this integral is asking us to find the area between π of π₯ and the π₯-axis from π all the way to negative infinity.
00:05:31.030 --> 00:05:33.920
Now, this is very similar to the integrals to going to positive infinity.
00:05:34.200 --> 00:05:37.670
Sometimes, its integral may converge, and sometimes, it may diverge.
00:05:38.180 --> 00:05:48.520
In the cases where it converges, we can say that it is equal to the limit as π‘ tends to negative infinity of the integral from π‘ to π of π of π₯ with respect to π₯ for π‘ is less than π.
00:05:49.100 --> 00:05:52.100
Now, this formula works very, very similar to the one we saw earlier.
00:05:52.320 --> 00:05:56.890
The main difference is that instead it is our lower bound that is infinite and it is negative infinity.
00:05:57.380 --> 00:06:00.850
Otherwise, this formula works very, very similar to the previous one.
00:06:01.420 --> 00:06:03.800
Letβs now look at an example of how it works.
00:06:04.490 --> 00:06:09.950
The integral from negative infinity to zero of two to the power of π with respect to π is convergent.
00:06:10.180 --> 00:06:11.470
What does it converge to?
00:06:12.250 --> 00:06:15.200
Now, we know a formula to evaluate integrals of this form.
00:06:15.790 --> 00:06:26.610
It tells us that the integral from negative infinity to π of π of π₯ with respect to π₯ is equal to the limit as π‘ tends to negative infinity of the integral from π‘ to π of π of π₯ with respect to π₯.
00:06:27.250 --> 00:06:29.990
In our case, we can see that π is equal to zero.
00:06:30.510 --> 00:06:33.960
We are in fact integrating with respect to π instead of respect to π₯.
00:06:34.150 --> 00:06:39.310
Therefore, our function π of π₯, or in our case, π of π, is two to the power of π.
00:06:39.700 --> 00:06:41.760
We can substitute these values into our formula.
00:06:42.400 --> 00:06:54.190
We now have that the integral from negative infinity to zero of two to the power of π with respect to π is equal to the limit as π‘ tends to negative infinity of the integral from π‘ to zero of two to the power of π with respect to π.
00:06:54.810 --> 00:06:56.500
Letβs start by finding this integral.
00:06:57.000 --> 00:06:58.790
We can consider the antiderivative.
00:06:59.100 --> 00:07:05.930
If we try differentiating two to the power of π with respect to π, then we obtain the natural logarithm of two multiplied by two to the power of π.
00:07:06.300 --> 00:07:12.780
Since the natural logarithm of two is a constant, we can divide by it on both sides and we can put it inside the differential.
00:07:13.130 --> 00:07:18.970
And we obtain that the derivative of two to the power of π of the natural logarithm of two is equal to two to the power of π.
00:07:19.540 --> 00:07:22.690
And so, here, we found the antiderivative of two to the power of π.
00:07:23.250 --> 00:07:26.030
Itβs two to the power of π over the natural logarithm of two.
00:07:26.350 --> 00:07:36.600
And we can use this to say that the integral from π‘ to zero of two to the power of π with respect to π is equal to two to the power of π over the natural logarithm of two from π‘ to zero.
00:07:37.190 --> 00:07:44.600
Since zero is the upper bound, when we substitute it in, the sign remains the same, giving us two to the power of zero over the natural logarithm of two.
00:07:44.840 --> 00:07:52.040
And since π‘ is the lower bound, when we substitute it in, we must change the sign, giving us negative two to the power of π‘ over the natural logarithm of two.
00:07:52.480 --> 00:07:57.020
Since anything to the power of zero is one, we can rewrite to use the power of zero as one.
00:07:57.440 --> 00:08:04.580
Therefore, we evaluated that this integral is equal to one over the natural logarithm of two minus two to the power of π‘ over the natural logarithm of two.
00:08:04.990 --> 00:08:07.850
And we can substitute this value for our integral back into our limit.
00:08:08.310 --> 00:08:11.530
Weβre able to use the properties of limits in order to split this limit up.
00:08:11.780 --> 00:08:26.910
We have for the limit of a difference of functions is equal to the difference of the limits of the functions, giving us that our limit is equal to the limit as π‘ tends to negative infinity of one over the natural logarithm of two minus the limit as π‘ tends to negative infinity of two to the power of π‘ over the natural logarithm of two.
00:08:27.160 --> 00:08:33.280
Now, in our first limit here, weβre taking the limit of one over the natural logarithm of two, which has no π‘ dependence.
00:08:33.430 --> 00:08:36.860
Therefore, this limit is simply equal to one over the natural logarithm of two.
00:08:37.140 --> 00:08:39.890
Weβre able to apply another limit property to the second limit.
00:08:40.410 --> 00:08:44.970
And that is that the limit of a quotient of functions is equal to the quotient of the limit of the functions.
00:08:45.470 --> 00:08:48.500
Now in the denominator here, weβre taking the limit of a constant function.
00:08:48.770 --> 00:08:51.910
Therefore, the denominator is simply equal to the natural logarithm of two.
00:08:52.270 --> 00:08:56.480
In the numerator, we have the limit as π‘ tends to negative infinity of two to the power of π‘.
00:08:56.680 --> 00:08:59.130
Here, π‘ is getting more and more negative.
00:08:59.570 --> 00:09:03.540
Therefore, two to the power of π‘ will be getting closer and closer to zero.
00:09:03.980 --> 00:09:09.460
And so, we can say that the limit as π‘ tends to negative infinity of two to the power of π‘ must be zero.
00:09:09.910 --> 00:09:20.860
Here, we reach our solution which is that the integral from negative infinity to zero of two to the power of π with respect to π converges to β and is therefore equal to β one over the natural logarithm of two.
00:09:23.210 --> 00:09:28.320
Next, weβll be combining the two formula weβve seen in this video so far in order to form a third formula.
00:09:28.850 --> 00:09:46.160
Weβll be using the property of integration that tells us how to integrate a function over adjacent integrals, which tells us that the integral from π to π of π of π₯ with respect to π₯ is equal to the integral from π to π of π of π₯ with respect to π₯ plus the integral from π to π of π of π₯ with respect to π₯.
00:09:46.500 --> 00:10:04.690
What this formula tells us is that if weβre trying to find the area between some π of π₯ and the π₯-axis between two points π and π, then this area will be equal to the sums of the areas between π of π₯ and the π₯-axis between π and π and π and π.
00:10:05.780 --> 00:10:10.990
Letβs consider the integral from negative infinity to infinity of π of π₯ with respect to π₯.
00:10:11.480 --> 00:10:21.390
If we have some π of π₯, as shown here, then this integral represents the area between π of π₯ and the π₯-axis, from negative infinity to positive infinity.
00:10:22.010 --> 00:10:27.810
And using the property of integrals over adjacent intervals, we can pick any value π on the π₯-axis.
00:10:27.940 --> 00:10:53.450
And our integral from negative infinity to positive infinity will be equal to the sum of the integrals from negative infinity to π and from π to positive infinity, giving us this following formula, which is that the integral from negative infinity to positive infinity of π of π₯ with respect to π₯ is equal to the integral from negative infinity to π of π of π₯ with respect to π₯ plus the integral from π to positive infinity of π of π₯ with respect to π₯.
00:10:53.990 --> 00:10:56.940
Now, we know formulas for evaluating both of these integrals.
00:10:57.100 --> 00:11:14.810
We can use them here to say that the integral from negative infinity to positive infinity of π of π₯ with respect to π₯ is equal to the limit as π tends to negative infinity of the integral from π to π of π of π₯ with respect to π₯ plus the limit as π‘ tends to infinity of the integral from π to π‘ of π of π₯ with respect to π₯.
00:11:15.390 --> 00:11:19.500
And here, π must be less than π and π‘ must be greater than π.
00:11:19.760 --> 00:11:28.010
Here, we have changed the π‘ from the first limit to an π to avoid confusion since one of the limits is tending to negative infinity and the other to positive infinity.
00:11:28.730 --> 00:11:31.790
And letβs also note that π can be any real number.
00:11:32.400 --> 00:11:35.120
We can use this formula to help us solve the following problem.
00:11:36.150 --> 00:11:43.920
The integral between negative infinity and positive infinity of π₯ multiplied by π to the power of negative π₯ squared with respect to π₯ is convergent.
00:11:44.350 --> 00:11:45.690
What does it converge to?
00:11:46.500 --> 00:11:49.550
We have a formula which can help us to evaluate integrals of this form.
00:11:49.960 --> 00:12:09.990
The formula tells us that the integral from negative infinity to positive infinity of π of π₯ with respect to π₯ is equal to the limit as π tends to negative infinity of the integral from π to π of π of π₯ with respect to π₯ plus the limit as π‘ tends to positive infinity of the integral from π to π‘ of π of π₯ with respect to π₯, where π can be any real number.
00:12:10.660 --> 00:12:16.420
Now, in our case, π of π₯ is equal to π₯ multiplied by π to the power of negative π₯ squared.
00:12:17.590 --> 00:12:19.650
So we can substitute this into our formula.
00:12:19.860 --> 00:12:22.160
Now, we can pick π to be any real number.
00:12:22.390 --> 00:12:24.100
Letβs choose π to be zero.
00:12:24.470 --> 00:12:27.020
However, you can pick any value of π that you like.
00:12:27.520 --> 00:12:29.400
Letβs now try to solve our integrals.
00:12:29.790 --> 00:12:35.100
And we can do this by trying to find the antiderivative of π₯ multiplied by π to the negative π₯ squared.
00:12:35.490 --> 00:12:42.620
We notice that the derivative of π to the power of negative π₯ squared is equal to negative two π₯π to the power of negative π₯ squared.
00:12:43.050 --> 00:12:46.730
Now, we can divide both sides of this equation by the constant term negative two.
00:12:47.060 --> 00:12:48.160
And we obtain this.
00:12:48.480 --> 00:12:51.960
On the left-hand side, we have a constant term multiplying a derivative.
00:12:52.160 --> 00:12:57.290
Using the derivative rule for scalar multiplication, we can move the negative one-half inside the derivative.
00:12:57.660 --> 00:13:02.120
And so, we found our antiderivative of π₯ multiplied by π to the power of negative π₯ squared.
00:13:02.700 --> 00:13:05.720
Itβs negative one-half π to the power of negative π₯ squared.
00:13:06.210 --> 00:13:09.940
Using this antiderivative, weβre able to evaluate the integrals inside our limits.
00:13:10.510 --> 00:13:13.430
Next, we can substitute in our upper and lower bounds.
00:13:13.900 --> 00:13:24.790
We obtained the limit as π tends to negative infinity of negative one-half multiplied by π to the power of negative zero squared minus negative one-half multiplied by π to the power of negative π squared.
00:13:25.350 --> 00:13:34.550
Plus the limit as π‘ tends to positive infinity of negative one-half multiplied by π to the power of negative π‘ squared minus negative one-half multiplied by π to the power of negative zero squared.
00:13:35.230 --> 00:13:46.220
Since π to the power of negative zero squared is simply π to the power of zero, which is just one, the negative one-half multiplied by π to the power of negative zero squared terms is simply negative one-half.
00:13:46.490 --> 00:13:49.810
And now, we can sort out the double negative signs which will give us a positive sign.
00:13:50.040 --> 00:13:56.900
Next, we can use one of the properties of limits, which tells us that the limit of a sum of functions is equal to the sum of the limits of their functions.
00:13:57.300 --> 00:13:59.760
And so, weβre able to split our limits up like this.
00:14:00.010 --> 00:14:02.460
Here, we have two limits of constant terms.
00:14:02.620 --> 00:14:05.240
So these limits are simply equal to that constant term.
00:14:05.580 --> 00:14:09.450
The first one being negative one-half and the second just being one-half.
00:14:09.810 --> 00:14:13.280
Therefore, when we add these two terms together, they will cancel out with one another.
00:14:13.800 --> 00:14:16.190
Now, we just need to worry about these two remaining limits.
00:14:16.560 --> 00:14:18.330
Letβs consider the one on the right first.
00:14:18.720 --> 00:14:24.750
As π‘ gets larger and larger and larger, negative π‘ squared will be getting larger and larger but in the negative direction.
00:14:25.130 --> 00:14:29.690
Therefore, π to the power of negative π‘ squared will be getting closer and closer to zero.
00:14:30.010 --> 00:14:35.850
And so, we can say that the limit as π‘ tends to infinity of negative one-half π to the power of negative π‘ squared is equal to zero.
00:14:36.250 --> 00:14:42.360
Similarly, as π gets larger and larger in the negative direction, π squared will be getting larger and larger in the positive direction.
00:14:42.710 --> 00:14:46.140
And so, negative π squared will be getting larger in the negative direction.
00:14:46.330 --> 00:14:50.380
And when this happens, π to the power of negative π squared gets closer and closer to zero.
00:14:50.820 --> 00:14:53.010
Therefore, this limit is also equal to zero.
00:14:53.500 --> 00:15:09.630
Since the negative one-half and the positive one-half canceled out with one another and these two limits are both equal to zero, therefore, we can say that the integral from negative infinity to positive infinity of π₯ multiplied by π to the power of negative π₯ squared with respect to π₯ converges to β and is therefore equal to β zero.
00:15:12.640 --> 00:15:17.010
We have now seen a variety of examples of how to evaluate limits with infinite bounds.
00:15:17.520 --> 00:15:19.820
Letβs recap some key points of this video.
00:15:20.710 --> 00:15:21.480
Key Points
00:15:21.660 --> 00:15:33.080
The integral from π to infinity of π of π₯ with respect to π₯ is equal to the limit as π‘ tends to infinity of the integral from π to π‘ of π of π₯ with respect to π₯, where π‘ is greater than π.
00:15:33.930 --> 00:15:45.790
The integral from negative infinity to π of π of π₯ with respect to π₯ is equal to the limit as π‘ tends to negative infinity of the integral from π‘ to π of π of π₯ with respect to π₯, where π‘ is less than π.
00:15:46.580 --> 00:16:05.500
And the integral from negative infinity to positive infinity of π of π₯ with respect to π₯ is equal to the limit as π tends to negative infinity of the integral from π to π of π of π₯ with respect to π₯ plus the limit as π‘ tends to positive infinity of the integral from π to π‘ of π of π₯ with respect to π₯, where π is any real number.
00:16:06.040 --> 00:16:11.770
And an integral with an infinite bound converges if the limit exists and diverges, if it does not.